(untitled) (Research, Society and Development, 2022)
Due to its function of assisting in the teaching-learning process of undergraduate students, student monitoring has been considered one of the most relevant pedagogical inventions of modernity. In this perspective, the aim of the present study was to carry out a comparative analysis of the approval and failure rates of students from two classes, in two different periods, of the Civil Engineering course of the Federal University of Southern and Southeastern Pará, Brazil – Unifesspa. To this end, data were collected from the classes of the subject Notions of Architecture and Urbanism, period 2019.2, which took place in person, without the presence of the student monitor, and from period 2020.5, which occurred remotely, with the presence of the monitor. After the comparative analysis, we found that the remote class period had a failure rate of 56%, which was higher than the rate in the in-person class period, which was only 15%. It was noted that the financial vulnerability of some students contributed to their failure in the remote learning system, since not all of them had the necessary technology to effectively carry out all the subject’s evaluations. Although the presented results showed a lower approval rate in the class with a monitor, the exchange of knowledge was mutual, enabling the teacher to pass on knowledge to the student monitor, thus allowing them to help the students of the subject, collaborating with teaching and promoting interactions between participants even in the remote system.